COVID-19 Lock-down Socio-economic Challenges Faced by Households in Rural Areas: A Perspective from Vhembe District, South Africa - Obaeko Iwara, Ishmael; Musvipwa, Faith; Ekene Amaechi, Kinsley; Raselekoane, Raymond (Sociološki pregled, 2020)
National responses to the COVID-19 pandemic have varied from country to country. In South Africa, the response has included a compulsory 21-day lock-down entailing restrictions of social and economic activities among other things. This arguably helped the country to avoid further spread of the virus, especially in townships, informal settlements and rural communities, where access to health facilities is often difficult. However, it has also exposed rural households to unforeseen challenges. This paper explores these challenges in view of proffering policy measures to help such households during subsequent lock-down. University students living within such rural households were purposively sampled to solicit electronic data from heads of households in Vhembe district. Using a qualitative method to analyze the data gathered from 82 households, five major issues emerged which include access to basic needs such as groceries, whereas water and health items were some of the challenges. The situation in households is further compounded by ‘limited source of income’ due to retrenchments and shutdown of subsistence businesses. ‘Depression and frustration’ emanating from the fear of contracting the virus, spousal domestic abuse, inability to meet home obligations, family squabbles as well as boredom caused by movement restriction also constitute part of the challenges. The lack of needed information regarding the virus, and ‘theft’ were other two challenges. Based on these findings, the paper recommends thorough consideration of the identified challenges before the enforcement of such lock-down. It also encourages more improvement to be made in the area of service delivery in rural communities.